Implementasi Kebijakan Rencana Kerja Tahun 2020 di Dinas Komunikasi, Informatika, Statistik dan Persandian Kabupaten Pangandaran - Thoyib Wahyudin (Jurnal Syntax Transformation, 2021)
The purpose of this research is the implementation of the 2020 work plan policy in the department of communication, informatics, statistics and persandian Pangandaran Regency. The research used is Qualitatative Research with a Descriptive Method approach. The implementation of the 2020 work plan policy in the Department of Communication, Informatics, Statistics and Persandian Pangandaran Regency, obtained the fact that at the implementation stage is still not supported by technical instructions in the form of Standard Operational Procedures in carrying out various activities that are the responsibility of each field and also the implementation of the work plan is more dominant depending on the Budget Implementation List or Budget Work Plan. Implementation of policies that have not been optimal, especially related to disposition factors, namely the placement of employees according to special skills and incentives. As for other factors relatively good enough, although it needs improvement in some aspects such as the same understanding of employees on the implementation of tasks, delegation of authority and division of duties. In terms of resources the number of employees is still felt inadequate and competence also needs to be improved, as well as the communication aspect must be more optimal so that there are similar understandings and actions to support the smooth implementation of tasks. The implementation of the 2020 work plan policy at the Department of Communication, Informatics, Statistics and Persandian Pangandaran district is arguably quite well run, although there are still variables or factors of policy implementation that have not been optimal, especially related to disposition factors, namely the placement of employees in accordance with special skills and incentives.